Genetics of resistance to northern leaf blight (Exserohilum tureicum) in maize (Zea mays) - Mahajan, V; Chandra, S; Verma, R N; Hussain, S M (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during the rainy season of 1990 and 1991 to study the genetics of resistance to northern leaf blight caused by Exserohilum tureicum (Pass.) Leonard & Suggs in maize (Zea mays L). Eight maize inbreds [‘(Stiff Slalk x Lanchester Line)-l-l-l’, 'Parbhat 12-1-2', 'CM 116', 'B 57 CM 202 B 57-18-1-1-1 #-1-1', 'Sartaj 11-1-1', 'B73 B79 # 3-2-1-1-1 #-5', 'CM 105' and 'MLY 1-1-2') were crossed in a half-dialel fashion. The resulting 28 FI progenies were evaluated at 2 planting dates (normal and late) at mid-altitude in 1990 and 1991 and at 2 planting dates (normal and late) at low altitude in 199 L Non-additive gene action was more prominent at mid-altitude in both the years and was influenced by the environment. Additive gene action was found more pronounced when analysed over low and medium altitudes, and this additive gene action was less influenced by the environment (altitude) than non-additive gene action. The inbred 'Parbhat 12-1-2' was found the best donor for resistance to northern leaf blight at mid-latitude.